Gutiérrez, Eduardo: "El Chaco". Buenos Aires, Librería Hachette S. A., 1960, 433 págs. - Herrera de Soria, María Eugenia (1961)
Fil: Herrera de Soria, María Eugenia. Universidad Nacional de Cuyo. Facultad de Filosofía y Letras